Researching peacebuilding in Africa : reflections on theory, fieldwork and context - Rashid, Ismail O. D., 1963-; Niang, Amy. (Routledge; London and New York:., 2021)
"This book examines the multifaceted nature of conflict and the importance of the socio-economic and political contexts of conflict and violence and shows how to support ongoing initiatives and programs to build sustainable peace on the African continent. Drawing on a range of conceptual framings in the study of peace and conflict, from gender perspectives to institutionalist to decolonial perspectives, the contributors show how peacebuilding research covers a whole range of questions that go beyond concerns for post-conflict reconstruction strategies. Chapters focus on the methodological, theoretical and practical aspects of peacebuilding and provide a toolbox of perspectives for conceptualizing and doing peacebuilding research in Africa. Anchored in African-centered perspectives, the book encourages and promotes high-quality interdisciplinary research that is conflict-sensitive, historically informed, theoretically grounded and analytically sound. This book will be of benefit to scholars, policy makers and research institutions engaged in peacebuilding in Africa"--
Includes bibliographical references and index.
Description based on print version record
Keywords: Peace-building -- Africa; Peace-building -- Africa -- International cooperation; Peace-building -- Methodology